PERAN BAITUL MAAL HIDAYATULLAH GERAI PROBOLINGGO DALAM PEMBERDAYAAN MASYARAKAT - Hasanah, Uswatun; Pertiwi, Fia Ayuning (JSE: Jurnal Sharia Economica, 2022)
According to the language zakat comes from the root word (masdar) from zakka which means blessing, growing, clean and good. Zakat means thaharah (clean), growth and barakah. This is in accordance with the word of Allah in Sura al-Tawbah verse 103. While the meaning of zakat shari'i is: "a certain part of a certain property, given to a certain person who is entitled to receive it as a form of worship and proof of obedience to Allah". Zakat management in Indonesia has been regulated in Law No. 23 of 2011, where the content is that zakat management is planning, implementing and coordinating activities in collecting, distributing and utilizing zakat. Indonesia has many zakat management institutions, one of which is Baitul Maal Hidayatullah (BMH). The Baitul Maal Hidayatullah National Amil Zakat Institute (BMH) is an amil zakat institution engaged in collecting zakat funds, infaq, alms, Waqf and Grants along with social humanitarian funds and corporate Corporate Social Responsibility (CSR), whose distribution is through educational, da'wah, social humanitarian and economic programs nationally which have been confirmed in 2001 by the Minister of Religious Affairs by issuing a Legality Decree. This study aims to find out how the role of Laznas Baitul Maal Hidayatullah Gerai Probolinggo in empowering the community through its programs. This research is a field research that uses observation methods and also uses library research methods. In fundraising zakat BMH, Probolinggo outlets have offline strategies (muzakki visit BMH offices directly), and online (utilizing social media). The distribution of BMH Probolinggo zakat distribution still holds the priority scale. Community empowerment programs are run through the fields of Education (scholarship assistance and school equipment for children in need), the field of da'wah (sending da'is to various regions and building several mosques), the social sector (providing basic food assistance for the poor and building boreholes in several regions), and the economic sector (mushroom cultivation in several areas of East Java). In addition, BMH also has an annual program, namely zakat fitrah in Ramadan and sacrifice during Eid al-Adha. Keywords: BMH, Community Empowerment, Zakat.